Methods of Credit to the Service Sphere by Commercial Bank (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Loans from commercial banks are of great importance in solving the existing problems of increasing the share of the service sector in the economy of our country, expanding and improving the quality of services provided, as well as in financial support of economic entities in this direction. This article examines the theoretical foundations of lending to the service sector, in particular scientific and theoretical views on improving the mechanism of lending to the service sector, forms of lending to the service sector and their specific features.